Penyerapan Tenaga Kerja Sektor Pertanian Tanaman Pangan pada Generasi Z - Bachtiar, Bayu Aji; Haq, Fika Sabila; Janah, Maidatul; Amalia, Novi Rizqi; Novaldi, Jeremia; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
The agricultural sector is one of the economic sectors that has a role in meeting food needs. The sustainability and development of agriculture certainly requires the contribution of generation Z who is the next generation of the nation. But this seems a little difficult considering that the employment of the agricultural sector is declining, especially in generation Z. Therefore, it is important to know what factors cause generation Z to no longer choose the agricultural sector as their main job and how these factors are related between provinces in Indonesia. The labor absorption of a region is influenced by other regions, meaning that there is spatial autocorrelation, so spatial analysis is carried out. The model used is Spatial Error Model (SEM), because there is dependency between dependent variables and there is error correlation between regions. The results of the analysis show that GDP per capita in the agricultural sector, land area, and average years of schooling have a significant effect on the number of workers in the agricultural sector. In contrast, the gender dominance of a region, and the Farmer Exchange Rate have no significant effect.